Guest editorial: Charlie Gard’s five months in court: better dispute resolution mechanisms for medical futility disputes - Pope, Thaddeus Mason (Journal of medical ethics, 2018)
British courts have adjudicated dozens of medical futility disputes over the past 10 years. Many of these cases have involved pediatric patients. All these judgements are publicly available in searchable legal reporters. And most were covered by the print or broadcast media.1 Yet, as noted by Dressler, none of these earlier cases received even a fraction of the public or scholarly attention that Charlie Gard has received (see page 453).One might assess the Gard case from two different perspectives. At one level, the Gard case is not unique. It is merely the n+1 medical futility dispute decided by the British courts. Admittedly, the Gard case has a much higher profile than earlier cases. But it announced no new rules or principles. It merely focused a spotlight on an already well-established process for resolving medical futility disputes.However, from another perspective, the Gard case is distinctive in at least five ways from other medical futility cases decided by the British courts. Because these unique features illustrate the limits or weaknesses of current rules and principles, they allude to potential improvements in the dispute resolution process. The papers in this special issue offer many valuable suggestions. After identifying the five unique features of the Gard case, I focus on the most prevalent two questions. Are courts the best forum for resolving these disputes? Is the best interest standard the right test for determining the limits of surrogate decision-making authority?Because the British courts have so many publicly available judgements in medical futility cases, it is possible to identify five distinctive features in the Gard case. First, Charlie’s parents were not asking GOSH clinicians to continue treating Charlie against either their professional judgement or against their personal beliefs. Instead, Charlie’s parents wanted to transfer him to another hospital that was willing …